2020
DOI: 10.1016/j.jtho.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

RET Solvent Front Mutations Mediate Acquired Resistance to Selective RET Inhibition in RET-Driven Malignancies

Abstract: Introduction: Novel rearranged in transfection (RET)-specific tyrosine kinase inhibitors (TKIs) such as selpercatinib (LOXO-292) have shown unprecedented efficacy in tumors positive for RET fusions or mutations, notably RET fusionpositive NSCLC and RET-mutated medullary thyroid cancer (MTC). However, the mechanisms of resistance to these agents have not yet been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
168
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(173 citation statements)
references
References 26 publications
2
168
0
3
Order By: Relevance
“…colleagues 17 reported RET G810 solvent front mutations as a mechanism of resistance to selpercatinib in five patients with RET fusion-positive NSCLC and RET-mutant medullary thyroid cancer, predicted to hinder drug binding based on structural modeling. However, the frequency of these RET mutations remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…colleagues 17 reported RET G810 solvent front mutations as a mechanism of resistance to selpercatinib in five patients with RET fusion-positive NSCLC and RET-mutant medullary thyroid cancer, predicted to hinder drug binding based on structural modeling. However, the frequency of these RET mutations remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low prevalence and narrow spectrum of RET mutations may reflect the high anti-RET potency of selpercatinib and pralsetinib, although our findings will require validation in larger cohorts. Interestingly, despite the potency of pralsetinib and selpercatinib against the gatekeeper RET V804 mutations based on preclinical studies, 13,14 the study by Solomon et al 17 identified RET V804 and G810 mutations in trans in two selpercatinib-resistant cases and in cis in a minority of reads in one selpercatinib-resistant case. Further studies are needed to elucidate whether the gatekeeper mutations can confer resistance to selpercatinib and/or pralsetinib despite the preclinical evidence, and whether the spectra of RET resistance mutations (and non-RET resistance alterations) differ between selpercatinib and pralsetinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that RET solvent-front mutations ( RET G810S/G810R/G810C) can cause on-target resistance to selective and multikinase RET inhibitors. 22 A better understanding of mechanisms of acquired resistance to selective RET inhibitors and frequency of resistant alterations would guide the development of novel agents and combination therapies directed towards further improvement of treatment outcomes for patients with RET-altered malignancies.…”
Section: Discussionmentioning
confidence: 99%